Polyketides from marine-derived Aspergillus welwitschiae inhibit Staphylococcus aureus virulence factors and potentiate vancomycin antibacterial activity in vivo. (June 2020) - Loges, Luciana A.; Silva, Denise B.; Paulino, Gustavo V.B.; Landell, Melissa F.; Macedo, Alexandre J.
Abstract: Staphylococcus aureus, a major cause of nosocomial and community associated infections, is becoming increasingly resistant to antibiotics. S. aureus infections are frequently biofilm-associated, and a diverse spectrum of virulence factors are determinant in the pathogenicity, which can be an interesting target resulting in less selective pressure for bacterial resistance. This study reports anti-virulence activity against S. aureus, including a MRSA clinical isolate, of naphto-γ-pyrones from Aspergillus welwitschiae mycelium, and the characterization of chemical constituents by LC-DAD and LC-MS. A remarkable decrease in biofilm formation, hemolysis and coagulation promoted by Staphylococcus aureus, important traits for bacterial pathogenicity, were observed. Furthermore, advantageous association with vancomycin resulted in significant protection against staphylococcal infection in Galleria mellonella model. These findings corroborate the importance of natural products as a source of new therapeutic possibilities, as well reveals potential alternatives for infection control using anti-virulence and drug association approaches. Highlights: Naphto-γ-pyrones from A. welwitschiae prevented S. aureus biofilm formation without interfering in bacterial growth. Hemolysis and plasma coagulation, important bacterial virulence traits, were also significantly affected. Synergistic effect in association with vancomycin was observed in an in vivo Galleria mellonella infection model.